Smotri, vsebine in metode pouka slovenske književnosti - Krakar-Vogel, Boža (Jezik in slovstvo, 1989)
The study points to the basic aims, content and the methods in the modern teaching of (Slovene) literature in elementary and secundary schools. It finaly also stresses the need for the new awarness of the value of literary didactics, which enables a higer level in the teaching of literature.
Keywords: književna didaktika; didactic method; didaktika; Slovene literature; slovenska književnost; metodika pouka